Brain drain and reverse brain drain: individual decision making and implications for economic growth - Hua, Kuo-Ting, author; Fan, Chuen-Mei, advisor; Cutler, Harvey, committee member; Kling, Robert W., committee member; Loomis, John B., committee member (Colorado State University. Libraries, 2011)
In two models, this dissertation explores two different but related topics in the international migration of skilled individuals, namely, the possibility of beneficial brain drain arises from the out-migration of skilled individuals and the potentially economic incentives for the emigrants to return to their homeland. The first model is a R&D and human capital accumulation hybrid endogenous growth model with a modified human capital accumulation behavior. It shows that an individual learns from previous innovations and that human capital accumulation fuels improvement in the quality of goods to promote economic growth. Since the ability of an individual is the key to the formation of human capital, the economic growth rate is tied to the representative individual's ability. It also shows that, with the presence of uncertainty about the opportunity of migration, the sending country could benefit from brain drain even without the scale effect. The second model is a two-period overlapping generation human capital growth model with a common self-selection fashion. Each individual optimally chooses his human capital level and the location he works. It shows that an increase in the probability of migration induces human capital accumulation in the sending country resulting from more individuals becoming potential returnees, and each potential emigrant or returnee acquiring more education. It also shows that the domestic investment opportunity could further increase human capital acquisition for an potential returnee while the wage premium couldn't.
Keywords: brain drain; R&D; human capital; economic growth